WATU GOYANG: WISATA NEGERI KHAYANGAN (PENGEMBANGAN DESA WISATA TAPAK TILAS SULTAN AGUNG, MANGUNAN) - Tanto Lailam; Awang Darumurti; Ani Yunita (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Community service program focused on developing competitive and cultured leading of tourism village. The partner of this service is